Crosslinked p(MMA) particles by RAFT emulsion polymerisation: tuning size and stability. Issue 28 (29th June 2022) - Marsden, Catherine J.; Breen, Colum; Tinkler, James D.; Berki, Thomas R.; Lester, Daniel W.; Martinelli, Jonathan; Tei, Lorenzo; Butler, Stephen J.; Willcock, Helen
Abstract : The size and stability of p(PEG)- b -p(MMA) block copolymer particles is tuned. Robust particles between 33–176 nm are formed and the use of a PEG methacrylate monomer with a methyl ether end group results in the most well defined and stable particles. Abstract : The controlled synthesis of amphiphilic di-block copolymers allows a large array of nanostructures to be created, including block copolymer particles, which have proved valuable for biomedical applications. Despite progress in targeting specific block copolymer architectures, control over the size and stability of spherical particles is less well explored. Here, we report the use of RAFT emulsion polymerisation to synthesise a library of p(MMA) particles, crosslinked with ethylene glycol dimethacrylate and stabilised by brush-like poly(ethylene glycol)-based polymers. We successfully synthesised a range of block copolymer particles, offering stability up to p(MMA)1000, with DLS reporting stable particle diameters of 33–176 nm and PDI < 0.2. DLS and AFM studies showed a general increase in particle diameter with increasing amounts of p(MMA). The use of a PEG methacrylate monomer with a methyl ether end group resulted in more well defined and stable particles than those with hydroxyl end groups. The copolymerisation of a suitably functionalized Gd(iii ) complex into the shell of the spherical p(MMA) particles resulted in Gd-loaded particles that were investigated in detail by 1 H NMR relaxometry, demonstrating that the Gd complex was successfully incorporated into the particles. This study will inform the synthesis of core–shell particles with optimised stability and targeted sizes, and show a simple method to incorporate a molecular sensor, generating a macromolecular imaging agent.